Measuring labor market discrimination against LGTBQ+ in the case of Ecuador: A field experiment - Wladimir Zanoni; Hugo Hernández; Omar Zambrano; Gabriel Quiroz (Inter-American Development Bank (IDB), 2023)
This paper presents the findings of an artifactual field experiment conducted in urban Ecuador to investigate discrimination against LGBTQ+ (here restricted to individuals self-identified as gay or lesbian) job seekers in the labor market. Focusing on occupations and sectors where LGBTQ + and non-LGBTQ + individuals commonly apply, the study employed fictitious job applications evaluated by 394 human resource analysts. The results indicate that, on average, LGBTQ+ candidates did not face discrimination in terms of hiring recommendations, job fit assessments, or wage offers. However, a closer analysis reveals a gender-based differential treatment. Female LGBTQ+ candidates received positive discrimination, were more likely to be selected and offered higher wages compared to their heterosexual counterparts. In contrast, male LGBTQ+ candidates experienced negative discrimination and no wage differences with a lower likelihood of selection. The study found an influential role of female recruiters in driving these discriminatory behaviors. These findings contribute to our understanding of the complex dynamics of discrimination towards LGBTQ+ workers in the labor market and its interaction with gender.
Keywords: J15; J16; C9; 330; Discrimination; LGBTQ+; Employment; Field experiments